FUTSAL TECHNICAL-TACTICAL TRAINING SESSIONS STRUCTURE FOR BEGINNERS (10 TO 13 YEARS OF AGE) (Fiep Bulletin - online, 2015)
This descriptive-exploratory study was accomplished with the objective ofanalyzing the procedures adopted by Futsal coaches beginners to transform objectives and contents in activities and tasks of technical-tactical training. In this study participated males Futsal players, divided into two categories 10 and 11 years, and 12 and 13 years, and respective coaches of 3 teams, in each category, of local clubs in the city of Florianópolis-SC. The instrument for collection of the data was the systematic and direct observation of the training sessions with a video-camera and subsequent transcription, according to Nascimento and Barbosa (2000). Data of 10 training sessions of each team were collected, in different training periods, during the sporting season of 2001, being identified, and registered 342 activities. The obtained results indicate that most of the time spends, in the sessions training, were with game activities (34.3%), and technicial training (28.5%). The technical activities constitute the largest concern of these formation steps (63.7% of the activities). The progressions of more frequent exercises were exercises of retaining technique, followed by competiting exercises. However, to the conditions of accomplishment of the tasks be considered, it was verified there not to be sequential relationship of content among the exercises in most of the accomplished progressions. Besides, there were not criteria of success that happened on the correct accomplishment and result of the movement, whose duration of the activities was determined by the players' effort perception in relationship to the tasks and in agreement with the available time. The coach most frequent conduct was taking all the decisions, supervising to, and stimulating the development of the activities. Regarding structuring and the variability of the content of the sessions, the evidences found in the investigation seem not to confirm the existence of the coaches' concern of to increase the complexity of execution of the exercises gradually and to improve specific details of the tasks. In general, it can be affirmed that in the technicial-tactical training sessions organization and structure prevails a directive methodology, basically centered in the technical elements of the game. The evidences confirm the use of a learning traditional model in the methodology of the training. The organization of the sessions needs to be reviewed to favor the process of learning in relation to the practical situations of the game, to look for the diversity of contents and to implement the players' continuous formation on this sport modality.
Keywords: Sport training; Sport Pedagogy; Futsal